Third International Conference on Advances in Mechanical, Aeronautical and Production Techniques - MAPT 2015 2015
DOI: 10.15224/978-1-63248-059-0-65
|View full text |Cite
|
Sign up to set email alerts
|

Single Phase and Two Phase Pressure Drops Across Sudden Contraction in Horizontal Rectangular Minichannel

Abstract: This paper presents experimental investigations on the effects of liquid properties on pressure drop for both single-phase and two-phase flows through sudden contraction in horizontal rectangular minichannel. In order to know the effects, water and viscoelastic liquid, namely 0.1 wt% polyacrylamide (PAM) aqueous solution are selected as the working liquid, while air as the working gas. Liquid single-phase and air-liquid twophase flow experiments were conducted at room temperature using a horizontal rectangular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…A schematic diagram of the test facility in the present study is shown in Figure 1, being the same as that used in our previous study [13]- [16]. Pressurized air from a compressor pushed the test liquid in a tank and supplies it to the test channel.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A schematic diagram of the test facility in the present study is shown in Figure 1, being the same as that used in our previous study [13]- [16]. Pressurized air from a compressor pushed the test liquid in a tank and supplies it to the test channel.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Santoso et al [14]- [16] in our group have investigated two-phase flow characteristic in rectangular minichannel with sudden expansion and sudden contraction in a horizontal plane. The cross-sectional sizes of the channel were from 3.09 mm by 2.79 mm to 5.98 mm by 2.95 mm for the sudden expansion and vice versa for the sudden contraction.…”
Section: Introductionmentioning
confidence: 99%